Standar konversi ukuran rumah tangga (URT) kedalam nilai zat gizi di pedesaan Kecamatan Simpang Tiga Aceh Besar - Agus Hendra Al Rahmad; Dedy Rusmawar; T Khairul Fadjri; Masyudi Masyudi (Politeknik Kesehatan Kemenkes Aceh, 2019)
Background:Household Size (HSM) is a measure often used to measure the amount of food consumed. Equipment used in specific households according to certain areas. In the 2014 Aceh Total Diet Survey report, public consumption was 74.1% and toddlers were quite good at 96.9%. The use of household size is not all regions have the same size in measuring food so that it can affect the consumption adequacy assessment. Objectives: The research aims to describe the use of household size tools used by rural area in Simpang Tiga District, Aceh Besar.Methods:Research has used cross-sectional research designs through qualitative and quantitative approaches. The study was conducted in September - October 2016 with a sample of 108 households in the Simpang Tiga District area. Primary data collection such as sample characteristics, type of household size, and food weight were carried out by interview and observation. Data processing namely editing, coding, entry using Nutry Survey and Epi Data, cleaning data entry. Analysis is only done descriptively.Results: The HSM used in community groups varies greatly. Carbohydrate sources are milk cans, coconut shells / kai, plastic cups, plastic basins and rice boxes, for animal protein there are no special household size tools used by the community, community vegetable protein sources use household duralex glass size measuring devices, milk cans , coconut shells / kai, and scales, there are only types of community fat sources used to measure coconut milk namely duralex glassConclusion: HSM units in units of weight (grams) in various types of food based on the nutrients studied are not all of them having the same weight value (grams). Suggestions, it is necessary to compile a list of needs and adequacy analysis of energy and nutrient values based on household size in estimating the nutritional value of Acehnese consumption.